Reporting Fatwa In The Media: Reception And Perception - Suria Hani A. Rahman; Noor Adzrah Ramle; Safiyyah Ahmad Sabri; Nur Kareelawati Abd. Karim; Mazni Buyong (Universiti Sains Islam Malaysia, 2024)
News coverage on Islam in newspaper publications in Malaysia has become part of Malaysian dailies since Islam is the official religion in Malaysia. A special section is allocated for Islamic teaching, forum or letter to Editors for certain days in a week. Perhaps the greatest innovation in coverage on Islam can be seen from how Malaysian reporters frame their stories, which many include the definition of religion, faith and moral choices in the secular world. News on Fatwa has, in short, become a major topic of discussion among Malaysian public once it is highlighted. It became an agenda for a period of time in most of the mainstream newspapers. This paper focuses on how the public perceived the news reporting made on fatwa in the Malaysian newspapers by looking at (i) the source of knowledge of the respondents, (ii) knowledge and understanding on fatwa, and (iii) correlation between level of education and understanding of fatwa news. Random samples of fatwa news on various issues were used as reference for the respondents. Then, a survey on 500 respondents was conducted randomly among Muslim public around Kuala Lumpur and the state of Selangor areas. This has helped in identifying the level of understanding and reactions of the public towards Fatwa issued by the National Fatwa Council of Malaysia. The findings also suggested small numbers of the news coverage on Fatwa has emphasized the significance of the Fatwa which, in the opinion of many far exceeds the important of the fatwa itself. This study may help to strategize the Fatwa Council in convincing the general public on Fatwa through news reporting because there had always been questions of reliability since there is no follow-up by the council to the public regarding Fatwa that has been issued by them.